Membrane Complexes of Syntrophomonas wolfei Involved in Syntrophic Butyrate Degradation and Hydrogen Formation - Crable, Bryan R.; Sieber, Jessica R.; Mao, Xinwei; Alvarez-Cohen, Lisa; Gunsalus, Robert; Ogorzalek Loo, Rachel R.; Nguyen, Hong; McInerney, Michael J. (Frontiers in Microbiology, 2016)
Syntrophic butyrate metabolism involves the thermodynamically unfavorable production of hydrogen and/or formate from the high potential electron donor, butyryl-CoA. Such redox reactions can occur only with energy input by a process called reverse electron transfer. Previous studies have demonstrated that hydrogen production from butyrate requires the presence of a proton gradient, but the biochemical machinery involved has not been clearly elucidated. In this study, the gene and enzyme systems involved in reverse electron transfer by Syntrophomonas wolfei were investigated using proteomic and gene expression approaches. S. wolfei was grown in coculture with Methanospirillum hungatei or Dehalococcoides mccartyi under conditions requiring reverse electron transfer and compared to both axenic S. wolfei cultures and cocultures grown in conditions that do not require reverse electron transfer. Blue native gel analysis of membranes solubilized from syntrophically grown cells revealed the presence of a membrane-bound hydrogenase, Hyd2, which exhibited hydrogenase activity during in gel assays. Bands containing a putative iron-sulfur (FeS) oxidoreductase were detected in membranes of crotonate-grown and butyrate grown S. wolfei cells. The genes for the corresponding hydrogenase subunits, hyd2ABC, were differentially expressed at higher levels during syntrophic butyrate growth when compared to growth on crotonate. The expression of the FeS oxidoreductase gene increased when S. wolfei was grown with M. hungatei. Additional membrane-associated proteins detected included FoF1 ATP synthase subunits and several membrane transporters that may aid syntrophic growth. Furthermore, syntrophic butyrate metabolism can proceed exclusively by interspecies hydrogen transfer, as demonstrated by growth with D. mccartyi, which is unable to use formate. These results argue for the importance of Hyd2 and FeS oxidoreductase in reverse electron transfer during syntrophic butyrate degradation.